ANALISIS KADAR AIR DAN KADAR ABU TEH BERBAHAN DASAR DAUN LAMUN ( Enhalus acoroides) - Tuapattinaya, Prelly M; Simal, Rufiati; Warella, Juen Carla (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: Seagrass is one of the components that make up this diversity. In addition to fruit and seeds, other parts of the seagrass plant, Enhalus acoroides, the opportunity to utilize seagrass as an alternative food base is very large and has the potential to be processed into innovative foods such as herbal teas. Methods: Testing the Moisture Content by means of a porcelain cup dried in an oven at 105˚C for 3 hours, after that it was weighed, added as much as 100g of samples of Seagrass tea extract (Enhalus acoroides) and placed in an oven at 105˚C for 3 hours. The weight of the cup and sample was weighed. The ash content was tested in the same way, except that 1-2 g of the sample was used and then dried in an electric furnace at 600˚C for 18-24 hours. Samples that have become ash are weighed. Results: The results of the analysis of the water content of seagrass tea (Enhalus acoroides) obtained the value of the water content of seagrass tea ranging from 9.17%-9.18%. The average value of the water content of seagrass tea is 9.17%. The results of the analysis of the ash content of seagrass tea (Enhalus acoroides) obtained that the water content of seagrass tea ranged from 18.52%-18.56%. The average value of the water content of seagrass tea is 18.53%. Conclusion: From the data obtained, it can be concluded that the water content of Seagrass Tea (Enhalus acoroides) is 9.17% and the Ash content of Seagrass Tea (Enhalus acoroides) is 18.53%.